Trade-Offs in Choosing a College Major - Michael Kaganovich (Center for Economic Studies and ifo Institute (CESifo), 2023)
Recent empirical analyses reveal substantial differences in the choices of college majors between demographic and socio-economic groups that are further amplified upon students' adjustment of their educational choices in the course of studies. The best documented and salient are the differences between genders, whereby women tend to be significantly underrepresented in some quantitatively oriented academic fields such as STEM, Business, and Economics, which also happen to be associated with relatively more lucrative careers, and overrepresented in others, such as Humanities and Education. Among potential explanations for this gender imbalance, some scholars noted that those more lucrative fields tend to have a more competitive environment and assign, on average, lower grades and conjectured that female students exhibit stronger aversion to low grades, hence their relative aversion to low-grading disciplines. The empirical literature also brings up a competing reasoning that gender biases in the choices of disciplines are directly driven by differences in preferences toward fields and pecuniary as well as non-pecuniary aspects of careers associated with them. This paper develops a theoretical model, which proposes a foundation for the latter explanation as a predominant one and reconciling it with the empirical evidence of gender differences in responsiveness to grades mentioned above. The paper argues that a student's responsiveness to grades, in terms of the initial choice of and persistence in majors, is field-specific and is the stronger, the weaker is the student's preferential attachment to the field. A key implication is that categories of students who attach high importance to pecuniary benefits of post-college careers, will be more tolerant toward inferior grades they may receive in the disciplines which promise such lucrative careers. It further explains why such students also tend to exhibit higher dropout rates from college.
Keywords: I23; I24; J24; D21; 330; higher education; college major; switching majors; dropout; gender gap